1994
DOI: 10.1183/09031936.94.07122174
|View full text |Cite
|
Sign up to set email alerts
|

The effects of indomethacin on refractoriness following exercise both with and without a bronchoconstrictor response

Abstract: T Th he e e ef ff fe ec ct ts s o of f i in nd do om me et th ha ac ci in n o on n r re ef fr ra ac ct to or ri in ne es ss s f fo ol ll lo ow wi in ng g e ex xe er rc ci is se e b bo ot th h w wi it th h a an nd d w wi it th ho ou ut t a a b br ro on nc ch ho oc co on ns st tr ri ic ct to or r r re es sp po on ns se e ABSTRACT: Repeated exercise tests demonstrate refractoriness to the development of exercise-induced asthma (EIA). It is unclear whether it is the initial exercise per se or the resulting broncho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In fact, pre-treatment with COX-inhibitors (e.g. indomethacine) significantly abolished refractoriness to repeated physical exercise, independent of intensity or the condition of inspired air [17,33]. No such inhibitor-induced suppression was observed in a study with repeated hyperpnea challenges [34], suggesting that exercise per se and not the level of ventilation might trigger release of protective PGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, pre-treatment with COX-inhibitors (e.g. indomethacine) significantly abolished refractoriness to repeated physical exercise, independent of intensity or the condition of inspired air [17,33]. No such inhibitor-induced suppression was observed in a study with repeated hyperpnea challenges [34], suggesting that exercise per se and not the level of ventilation might trigger release of protective PGs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one study showed that exercising with warm and humid air did not induce substantial EIB but this exercise was still effective in preventing EIB in the following exercise challenge [17]. From a practical point of view, however, warm-up exercise using warm and humid air is a technically challenging approach.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that pretreatment with inhalation of PGE 2 has been shown to inhibit the response to exercise challenge (25), as well as the inhibiting effect of nonsteroidal antiinflammatory drug pretreatment on the development of refractoriness (24,26,36), has led to the speculation that PGE 2 is the key mediator of refractoriness. However, there are no previous reports on increased excretion of PGE 2 following exercise challenge in asthmatic subjects, rather a decrease in the levels of PGE 2 has been seen in induced sputum (13).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested a decreased responsiveness to the released mediators at the level of the airway smooth muscle as one possible mechanism in refractoriness (21,22). Because nonsteroidal anti-inflammatory drugs almost completely abolish refractoriness (26), it has been proposed that PGE 2 may be of importance for the development of refractoriness (24,26,36). How-ever, there is to date no direct evidence for release of PGE 2 in vivo during the refractory period.…”
mentioning
confidence: 99%
“…48 This may be related to the endogenous production of prostaglandin-2, which actively relaxes airway smooth muscle. 49 Data from studies of vitamin C supplements have demonstrated that patients with asthma have decreased levels of ascorbic acid in their leukocytes. In a study of 20 asthmatic patients with EIB (mean age 13.8 years), each received 2 g of ascorbic acid 1 hour before exercise.…”
Section: Control Of Exercise-induced Bronchoconstriction Classic Thermentioning
confidence: 99%